Bringing eye care for children with learning disabilities and autism into special schools. (2nd June 2019) - O'Brien, Donna
Abstract : Children with learning disabilities are more likely to experience eye and vision problems and yet many are not accessing eye care. In January 2019, the NHS Long-Term Plan for England pledged to introduce dental, hearing and sight checks in special schools to address some of these health inequalities.